Relationship between common air pollutants with risk of cardio-respiratory hospitalization in urbanized areas in Kelantan - Mat Sahar Nurul Najwa; Ya’acob Siti Hajar; Hie Ling Wong; Nawawi Siti Aisyah; Awang Norrimi Rosaida (BIO Web of Conferences, 2023)
A high concentration of air pollution can lead to health problems which are the cardiovascular and respiratory systems (WHO, 2014). A study has been conducted to know the relationship between five criteria air pollutants with hospitalization related to cardiovascular and respiratory diseases in two cities in Kelantan. The secondary data from 2000 until 2015 analyzed in the study were obtained from DOE and MOH for the air pollutants concentration and hospitalization, respectively. This study shows that the mean concentration of all pollutants in the study area is below the RMAAQS. Significant Relative Risk (RR) values were found for cardiovascular hospitalization associated with SO2 (RR = 1.537, 95% CI = 2.970, 7.956), NO2 (RR = 1.212, 95% CI = 1.156, 1.272), and O3 (RR = 4.873, 95% CI = 2.768, 8.578). In contrast, significant RR for respiratory hospitalization was found to be associated with SO2 (RR = 1.952, 95% CI = 1.013, 3.762), NO2 (RR = 2.021, 95% CI = 6.170, 6.620), O3 (RR = 1.128, 95% CI = 4.427, 2.874), and PM10 (RR = 1.008, 95% CI = 1.007, 1.008). The highest value of Relative Risk is O3 and NO2 for hospitalization related to cardiovascular and respiratory diseases, respectively. In conclusion, the value of RR associated with air pollutants proves that air pollutants are associated with cardiovascular and respiratory-related hospitalization risk.